Study of The Dynamical Behavior For Deuterons in Dense Plasma Focus - Yonas, D. H.; Majeed, R.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The motion of fast deuterons in most dense plasma focus devices  ( DPF ) , may be characterized that it has a complex nature in its paths and this phenomena by describing a through gyrating motion with arbitrary changes in magnitude and direction .  In this research , we focused on the  understanding the theoretical concepts which  depend deeply on the experimental results to explain the deuteron motions in the pinch region , and then to use the fundamental physical formulas that are deeply related to the explanation of this motion to prepare a suitable model for calculating the vertical and radial components for deuteron velocity by improving the  Rung â€“ Kutta  Method